The electrical and photoluminescence characteristics of thermally deposited ALQ[3] films / Koay Jan Yeong - Koay, Jan Yeong (2010)
Low molecules organic materials are attracting much attention as a candidate for flat panel displays and semiconductor applications. The tris (8-hydroxyquinoline) aluminum (III) complex (Alq3), is the most important and widely studied material. However, there are still many things which remain to be studied. In this work, the effects of various surface treatments using CH4, He, Ar, O2 plasma and UV/O3 treatments on anode material surfaces (c-Si and ITO) have been studied on the photoluminescence and electrical properties of Alq3 films prepared by vacuum evaporation technique using an in-house designed and built deposition system. Photoluminescence (PL) and current-voltage (I-V) measurements were done to investigate these properties. The PL results demonstrated that the PL peak intensity and peak position of the deposited film was effected by the surface treatments done on the anode material surfaces. The Fowler-Nordheim (FN) model was used on the I-V plots to estimate the barrier height of the deposited films. The results showed that threshold voltage (VT), threshold current (JT), OLEDs driving voltage (Vd) and barrier height (ΦB) were effected on the various surface treatments done on the anode material surfaces. In general, the electrical and PL properties of Alq3 films on ITO are enhanced with UV/O3 treatment which is an establish technique used for cleaning ITO in ITO/Alq3/Al heterostructure. PL emission intensity of Alq3 films on ITO substrates also is enhanced with increase in O2 plasma treatment time on the ITO substrates. Electrical properties of ITO/Alq3/Al heterostructures improve with short duration O2 plasma treatment time on the ITO but are downgraded for long treatment time. Short duration He and Ar and plasma treatments remove hydrocarbon contamination on the ITO and c-Si substrate surfaces and this has the effect of increasing hole injection in ITO/Alq3/Al and p-type c-Si/Alq3/Al heterostructures. Long duration He and Ar plasma treatments on these substrates expose the treated substrate surface to prolonged ion bombardments producing a decrease in the PL emission intensity and hole injection in the ITO and c-Si anode heterostructures. The CH4 plasma treatment produces adverse effects on the electrical and PL properties of Alq3 films on these substrates as result of the formation of hydrocarbon layer.